A COMPARATIVE STUDY OF GPS-GUIDED TRACTOR AUTOSTEER VS. TRADITIONAL SEEDING TECHNOLOGIES ON MAIZE YIELD AND FUEL EFFICIENCY - Keolavong, Manivone; Vong, Soneva; Phommavong, Soukchinda (Techno Agriculturae Studium of Research, 2025)
This study compares the impact of GPS-guided tractor autosteer technology and traditional manual steering on maize yield and fuel efficiency. Precision agriculture technologies, such as GPS-guided autosteer, offer more accurate and efficient field operations, reducing overlaps and gaps in seeding, which are common in manual methods. However, there is limited empirical evidence on the agronomic and operational performance of these technologies in maize cultivation. The research was conducted on maize farms over one growing season, with two treatments: GPS-guided autosteer and traditional manual steering. Data on maize yield, fuel consumption, seeding accuracy, and operational time were collected and analyzed. The results showed that GPS-guided autosteer significantly improved seeding accuracy, reducing overlaps and leading to a 12% increase in maize yield compared to traditional methods. Additionally, fuel consumption was reduced by 18% due to more efficient coverage and reduced operational time. The autosteer system also demonstrated improved consistency in row spacing and plant population. This study concludes that GPS-guided autosteer technology offers both agronomic and economic advantages, increasing maize productivity, enhancing fuel efficiency, and promoting more sustainable, cost-effective farming practices.